Bibliometric analysis of scientific production on student adaptation to college - Faná del Valle Villar, Amalia; De la Rosa Ruiz, Daniel; Ibanez-Ayuso, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Adaptation to university life represents a major challenge for young people. Given the new difficulties added to this challenge because of COVID-19, the aim of this study is to analyse the scientific production on this issue over the last three decades (1991-2021). For this purpose, the bibliometric study has been combined with social network analysis techniques using Rstudio and Vosviewer software. A total of 291 articles from the Scopus database were analysed. The results provide a holistic view of this field and its evolution over time.